A Study on Effectiveness of Multimedia on Academic Achievement among High Academy Scholars - Ramachandran, Rehana; Selvakumar, Y Stanly (International Journal of Advanced Research in Peace, Harmony and Education; Vol 8 No 1 (2023): International Journal of Advanced Research in Peace, Harmony & Education, 2023)
The end of the present study is to explore the effect of multimedia instruction on academic achievement of high academy scholars located in and cities of Chennai. The real value of exploration is its capability to arrive at conclusions and conceptions grounded on the analysis and interpretations. The exploration was conducted on 300 high academy scholars in and cities of Chennai. The data was collected by using an applicable tool and anatomized by ‘t’ test. The present exploration shows that in changing from a traditional ‘chalk and talk system to multimedia instruction not simply enriches class room tutoring, it also significantly improves the academic achievement of scholars. It also implies that’ multimedia instruction proves to be more palpable in its effectiveness on achievement than the traditional system of instruction. It seems to be more practical and is extensively respectable to scholars. It also keeps in mind the individual differences and enables all types of scholars to perform better.